Population eye health education using augmented reality and virtual reality : scalable tools during and beyond COVID-19 - Gunasekeran, Dinesh Visv (2021)
The COVID-19 outbreak has had a massive impact on healthcare systems, with over 12 million infected individuals as of 10 July 2020.¹ This has necessitated operational overhaul in ophthalmology and other clinical specialties in accordance with public health measures such as physical distancing and cancellation of non-urgent clinical services.² The downstream impact of these measures include the disruption of healthcare functions including preventive programmes such as eye screening, which serve a crucial role to detect disease at early stages before the onset of irreversible morbidity such as visual impairment (VI).